Admission C-reactive protein concentrations are associated with unfavourable neurological outcome after out-of-hospital cardiac arrest - Christoph Schriefl (Nature Portfolio, 2021)
Abstract Whether admission C-reactive protein (aCRP) concentrations are associated with neurological outcome after out-of-hospital cardiac arrest (OHCA) is controversial. Based on established kinetics of CRP, we hypothesized that aCRP may reflect the pre-arrest state of health and investigated associations with neurological outcome. Prospectively collected data from the Vienna Clinical Cardiac Arrest Registry of the Department of Emergency Medicine were analysed. Adults (≥ 18 years) who suffered a non-traumatic OHCA between January 2013 and December 2018, without return of spontaneous circulation or extracorporeal cardiopulmonary resuscitation therapy were eligible. The primary endpoint was a composite of unfavourable neurologic function or death (defined as Cerebral Performance Category 3–5) at 30 days. Associations of CRP levels drawn within 30 min of hospital admission were assessed using binary logistic regression. ACRP concentrations were overall low in our population (n = 832), but higher in the unfavourable outcome group [median: 0.44 (quartiles 0.15–1.44) mg/dL vs. 0.26 (0.11–0.62) mg/dL, p < 0.001]. The crude odds ratio for higher aCRP concentrations was 1.19 (95% CI 1.10–1.28, p < 0.001, per mg/dL) to have unfavourable neurological outcome. After multivariate adjustment for traditional prognostication markers the odds ratio of higher aCRP concentrations was 1.13 (95% CI 1.04–1.22, p = 0.002). Sensitivity of aCRP was low, but specificity for unfavourable neurological outcome was 90% for the cut-off at 1.5 mg/dL and 97.5% for 5 mg/dL CRP. In conclusion, high aCRP levels are associated with unfavourable neurological outcome at day 30 after OHCA.